Business Ethics and the Effectiveness of Sustainability Reporting on Firm Performance (E-Jurnal Akuntansi, 2026)
The effectiveness of sustainability disclosure in improving corporate performance remains debated in the literature, particularly in the context of emerging markets. This study aims to examine the influence of sustainability reports on corporate performance and the moderating role of business ethics in this relationship. Secondary data were obtained from Bloomberg Terminal and MSCI Sustainability Analytics on 300 non-financial companies listed on the Indonesia Stock Exchange over the 2020–2024. The analysis used moderated regression analysis using the PROCESS Hayes Model. The test results indicate that sustainability reports have a significant positive effect on corporate performance, and business ethics have been shown to conditionally strengthen this influence. This finding is consistent across both accounting-based and market-based performance measures. This study confirms that the effectiveness of sustainability reports as a value creation instrument is conditionally determined by the quality of the corporate business ethics that underpin them
Keywords: Business Ethics; Corporate Performance; Sustainability Reporting; Stakeholder Theory